Determinants of persistent smoking among breast cancer survivors - Gali, Kathleen; Aryal, Sita; Bokemeyer, Frederike; Behrens, Sabine; Seibold, Petra Beate; Obi, Nadia; Becher, Heiko; Chang-Claude, Jenny (Preventive Medicine Reports, 2024)
INTRODUCTION: While quitting cigarette smoking can improve cancer treatment outcomes, many cancer patients continue to smoke post-diagnosis. The aim of this study was to examine factors associated with persistent cigarette use in postmenopausal women diagnosed with breast cancer, a cancer not traditionally thought of as tobacco-related. - METHODS: We used data of breast cancer patients who were recruited into the MARIE Study (Mamma Carcinoma Risk Factor Investigation) in Germany between 2002 and 2005 and followed up in 2009. This analysis was based on 450 study participants who reported active cigarette smoking at the time of diagnosis and participated in the follow-up interview. Logistic regression analyses were conducted to examine the association of sociodemographic characteristics, health behaviors, medical factors, and cancer treatment types with persistent smoking behavior. - RESULTS: At an average of 5.9 years (SD = 1.2) after diagnosis, 244 (54.2%) breast cancer survivors were still smoking cigarettes at follow-up. A longer duration of smoking (OR = 1.04, 95% CI = 1.01-1.06) and smoking on average ≥10 cigarettes per day (OR = 1.52, 95% CI = 1.02-2.28) increased the likelihood of persistent smoking, whereas increasing age (OR = 0.94, 95% CI = 0.90-0.97) and high engagement in leisure time physical activity (≥62 MET-hrs/wk: OR = 0.55, 95% CI = 0.32-0.98) were associated with quitting. - CONCLUSION: Smoking cessation programs in cancer care are needed. Specifically for breast cancer patients, tobacco treatment plans that include physical activity may be particularly helpful in quitting smoking cigarettes.
Gesehen am 12.06.2025